The Urgency of Religious-Blasphemy Case Arrangement in the Frame of Diversity towards National Criminal Law Reform - Somawijaya Somawijaya; Ajie Ramdan (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2018)
Indonesia is an independent state with One Godly Belief based on just civilized humanity. Amid the diversity, and to guarantee togetherness within the framework of state life, the state desperately needs the formulation of common goals or ideals commonly referred to as state philosophy or state ideals, which function as grodslag philosophies and common platform for citizens in the context of state life. This diversity is recognized on the Indonesian emblem of Garuda Pancasila ‘Bhinneka Tunggal Ika’. The notion of the importance of regulation regarding the criminal offense of blasphemy is the realization of the first principle in the Pancasila, namely the Belief in the One and Only God. This study analyzed the new Draft of the Criminal Code submitted by the Government to the Indonesian Parliament in mid-2015 to replace the Criminal Code that is inherited from the era of the Dutch Colonial. The new Draft of the Criminal Code contains important changes, namely the existence of reconciliation efforts and revitalization of blasphemy acts. This change becomes interesting to be examined, especially from the urgency of the existence of regulation on blasphemy in the frame of diversity and aspects of penal reform. It also explains that the issue of blasphemy is very sensitive in Indonesian society. Constitutional Court Decree Number 140/PUU-VII/2009 is the foundation of the re-conception and revitalization of blasphemy in Penal Reform.Urgensi Pengaturan Penodaan Agama dalam Bingkai Kebhinnekaan Menuju Pembaharuan Hukum Pidana NasionalAbstrakNegara Indonesia adalah negara yang berke-Tuhanan yang Maha Esa menurut dasar kemanusiaan yang adil beradab. Di tengah keberagaman dalam suatu masyarakat untuk menjamin kebersamaan dalam kerangka kehidupan bernegara diperlukan perumusan tentang tujuan-tujuan atau cita-cita bersama yang biasa disebut sebagai falsafah kenegaraan atau staatsidee (cita negara) yang berfungsi sebagai filosofische grodslag dan commonplatforms diantara sesama warga masyarakat dalam konteks kehidupan bernegara. Keberagaman tersebut tertulis pada lambang negara Indonesia Garuda Pancasila yaitu Bhineka Tunggal Ika. Pemikiran akan pentingnya pengaturan tentang tindak pidana penodaan agama karena ini merupakan  pewujudan dari sila pertama dalam Pancasila, yaitu Ketuhanan Yang Maha Esa. Artikel ini menganalisis Rancangan Kitab Undang-Undang Hukum Pidana (RKUHP) yang diajukan Pemerintah ke DPR RI pada pertengahan 2015 sebagai upaya mengganti Kitab Undang-Undang Hukum Pidana (KUHP) Warisan Kolonial Belanda. RKUHP memuat perubahan yang penting, yaitu adanya upaya rekonsepsi dan revitalisasi perbuatan penodaan agama (penistaan agama). Perubahan inilah yang kemudian menarik untuk diteliti, terutama dari urgensi keberadaan perbuatan penodaan agama dalam bingkai kebhinekaan dan aspek pembaharuan hukum pidana (penal reform). Artikel ini menjelaskan bahwa permasalahan penodaan agama adalah hal yang sangat sensitif dalam masyarakat Indonesia. Putusan MK No. 140/PUU-VII/2009 menjadi dasar penyusun RKUHP melakukan rekonsepsi dan revitalisasi perbuatan penodaan agama untuk memperbaharui KUHP. DOI: https://doi.org/10.22304/pjih.v5n3.a4